Virtualization in Networks A survey - Arif, Moiz; Nafis Khan, Abdullah; Iftikhar, Saad (Discoveries in Agriculture and Food Sciences, 2013)
Virtualization is considered an integral part of any network. Many new features and services can be introduced with a mere implementation in software and without deploying extensive hardware. In this survey we will be looking at the history and motivations that led to the realization of virtualization techniques. We will be studying its architecture, current technologies followed by challenges and future of virtualization. Keywords – Virtualization, VLAN, VPN, Cloud Computing, Virtualized Data Centers.